Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find the coefficient of [tex]\( x^2 \)[/tex] in the expansion of [tex]\( (x+2)^3 \)[/tex], let's start by expanding the expression:
[tex]\[ (x + 2)^3 \][/tex]
We can use the binomial theorem to expand this expression. The binomial theorem states that:
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]
In our case, [tex]\( a = x \)[/tex], [tex]\( b = 2 \)[/tex], and [tex]\( n = 3 \)[/tex]. Plugging these values into the binomial expansion, we get:
[tex]\[ (x + 2)^3 = \sum_{k=0}^{3} \binom{3}{k} x^{3-k} \cdot 2^k \][/tex]
Let's break this down term by term:
1. For [tex]\( k = 0 \)[/tex]:
[tex]\[ \binom{3}{0} x^{3-0} \cdot 2^0 = 1 \cdot x^3 \cdot 1 = x^3 \][/tex]
2. For [tex]\( k = 1 \)[/tex]:
[tex]\[ \binom{3}{1} x^{3-1} \cdot 2^1 = 3 \cdot x^2 \cdot 2 = 6x^2 \][/tex]
3. For [tex]\( k = 2 \)[/tex]:
[tex]\[ \binom{3}{2} x^{3-2} \cdot 2^2 = 3 \cdot x \cdot 4 = 12x \][/tex]
4. For [tex]\( k = 3 \)[/tex]:
[tex]\[ \binom{3}{3} x^{3-3} \cdot 2^3 = 1 \cdot 1 \cdot 8 = 8 \][/tex]
Now, combining all the terms, we get the expanded form:
[tex]\[ (x + 2)^3 = x^3 + 6x^2 + 12x + 8 \][/tex]
From this expanded form, we can see that the coefficient of [tex]\( x^2 \)[/tex] is [tex]\( 6 \)[/tex].
Thus, the coefficient of [tex]\( x^2 \)[/tex] in the expansion of [tex]\( (x+2)^3 \)[/tex] is:
[tex]\[ \boxed{6} \][/tex]
[tex]\[ (x + 2)^3 \][/tex]
We can use the binomial theorem to expand this expression. The binomial theorem states that:
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]
In our case, [tex]\( a = x \)[/tex], [tex]\( b = 2 \)[/tex], and [tex]\( n = 3 \)[/tex]. Plugging these values into the binomial expansion, we get:
[tex]\[ (x + 2)^3 = \sum_{k=0}^{3} \binom{3}{k} x^{3-k} \cdot 2^k \][/tex]
Let's break this down term by term:
1. For [tex]\( k = 0 \)[/tex]:
[tex]\[ \binom{3}{0} x^{3-0} \cdot 2^0 = 1 \cdot x^3 \cdot 1 = x^3 \][/tex]
2. For [tex]\( k = 1 \)[/tex]:
[tex]\[ \binom{3}{1} x^{3-1} \cdot 2^1 = 3 \cdot x^2 \cdot 2 = 6x^2 \][/tex]
3. For [tex]\( k = 2 \)[/tex]:
[tex]\[ \binom{3}{2} x^{3-2} \cdot 2^2 = 3 \cdot x \cdot 4 = 12x \][/tex]
4. For [tex]\( k = 3 \)[/tex]:
[tex]\[ \binom{3}{3} x^{3-3} \cdot 2^3 = 1 \cdot 1 \cdot 8 = 8 \][/tex]
Now, combining all the terms, we get the expanded form:
[tex]\[ (x + 2)^3 = x^3 + 6x^2 + 12x + 8 \][/tex]
From this expanded form, we can see that the coefficient of [tex]\( x^2 \)[/tex] is [tex]\( 6 \)[/tex].
Thus, the coefficient of [tex]\( x^2 \)[/tex] in the expansion of [tex]\( (x+2)^3 \)[/tex] is:
[tex]\[ \boxed{6} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.